Rheology modified slurries for electrochemical cells and components made therefrom - Patents.com

JP2024508111A5Pending Publication Date: 2025-02-19SOLID POWER OPERATING INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023548701
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-11
Filing Date
2022-02-11
Publication Date
2025-02-19

AI Technical Summary

Technical Problem

There is a need for more efficient methods of manufacturing electrochemical cells to meet the increasing demand for improved reliability, capacity, thermal performance, longevity, and recharging performance, particularly in lithium solid state battery technology, while also addressing safety and packaging efficiency.

Method used

Incorporation of poly(styrene-butadiene-styrene) block copolymers, poly(styrene-isoprene-styrene) block copolymers, and poly(styrene-ethylene-butylene-styrene) block copolymers as rheology modifiers in electrochemical cell layers, with amounts less than 5% by weight, along with specific binders and conductive additives, to enhance the manufacturing process without compromising performance.

Benefits of technology

The use of these rheology modifiers improves the processing efficiency of electrochemical cell layers, reducing the risk of mud cracking and enhancing the performance of electrochemical cells by maintaining high electrical and ionic conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Methods for making rheologically modified slurries and electrochemical cells made therefrom.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Various embodiments described herein relate to the fields of primary and secondary electrochemical cells, electrodes and electrode materials, electrolytes and electrolyte compositions, and corresponding methods of making and using the same. [Background technology]

[0002] This Patent Cooperation Treaty (PCT) patent application is related to and claims priority to U.S. patent application Ser. No. 63 / 148,444, entitled "Rheologically Modified Slurries for Electrochemical Cells and Components Made Therefrom," filed on February 11, 2021, the entire contents of which are incorporated herein by reference for all purposes.

[0003] The increasing number and diversity of mobile devices, the evolution of hybrid / electric vehicles, and the growth of Internet of Things (IOT) devices are driving the need for battery technologies with improved reliability, capacity (e.g., Ampere-hour (Ah) capacity), thermal properties, lifetime, and rechargeability. Currently, lithium solid-state battery technology offers the potential for improvements in these areas, as well as safety and packaging efficiency, while also enabling new high-energy chemistries. Summary of the Invention [Problem to be solved by the invention]

[0004] To meet this increasing demand, new and more efficient methods of manufacturing electrochemical cells are needed. [Means for solving the problem]

[0005] Provided herein is an electrochemical cell layer comprising one or more solid electrolytes and a rheology modifying component selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS), wherein the rheology modifying component is present in an amount less than 5% by weight of the composition of the electrochemical cell layer. In an exemplary embodiment, the rheology modifying component is present in an amount less than 2% by weight of the electrochemical cell layer.

[0006] In some embodiments, the electrochemical cell layer is a separator layer that includes at least one additional binder or polymer. In some embodiments, the binder or polymer is at least one polymer or binder selected from the group consisting of polystyrene, polyvinylidene fluoride (PVdF), and poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP).

[0007] In some embodiments, the electrochemical cell layer is a cathode layer further comprising a cathode active material, a binder or polymer, and a conductive additive. In some embodiments, the cathode active material is NMC, LiFePO 4 , LiCoO 2 , NCA, NMA, LMO, and iron sulfide. In some additional embodiments, the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0008] In some embodiments, the electrochemical cell layer is an anode layer that includes an anode active material, a binder or polymer, and a conductive additive. In some aspects, the anode active material is selected from the group consisting of Si, Si alloys, graphite, Sn, Li, and lithium alloys. In some additional aspects, the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0009] Further provided herein is a method of manufacturing an electrochemical cell. The method includes forming a slurry of a solid electrolyte; a rheology modifying component selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS); and a solvent; and coating the slurry onto a substrate to form an electrochemical cell layer. In some embodiments, the rheology modifying component is present in an amount of less than 2% by weight of the solid composition of the slurry. In some additional embodiments, the method further includes grinding the slurry before coating the slurry onto the substrate, where the rheology modifying component is added to other components of the slurry before grinding. In a further embodiment, the solid electrolyte is a sulfide solid electrolyte comprising a lithium compound, a phosphorus compound, and a halogen. In a further embodiment, the solvent is selected from the group consisting of benzene, toluene, xylene, heptane, and isobutyl isobutyrate.

[0010] In some embodiments, the electrochemical cell layer is a cathode layer and the slurry further comprises a cathode active material, a binder or polymer, and a conductive additive. In some embodiments, the cathode active material is NMC, LiFePO 4 , LiCoO 2, NCA, NMA, LMO, and iron sulfide. In some additional embodiments, the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0011] In some embodiments, the electrochemical cell layer is an anode layer and the slurry further comprises an active material, a binder or polymer, and a conductive additive. In some aspects, the anode active material is selected from the group consisting of Si, Si alloys, graphite, Sn, Li, and lithium alloys. In some additional aspects, the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0012] Further provided herein is a composition comprising a solvent, a solid electrolyte, a binder or polymer, and one or more rheology modifying components selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS; herein styrene-butadiene-styrene rubber, also referred to as "SBR"), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS), wherein the composition has a viscosity of about 100 cP to about 5000 cP (about 0.1 Pa·s to about 5 Pa·s). In some embodiments, the composition further comprises one of a cathode active material or an anode active material, and a conductive additive. In some additional embodiments, the composition has a solids to solvent ratio of about 10% to about 90% by weight. [Brief description of the drawings]

[0013] The present disclosure may be understood by reference to the following detailed description taken in conjunction with the drawings, which are briefly described below: It should be noted that for purposes of clarity of illustration, certain elements in the drawings may not be drawn to scale.

[0014] [Figure 1] FIG. 1 is a simplified schematic diagram of a layer structure of an electrochemical cell according to an embodiment.

[0015] [Diagram 2] FIG. 2 is a flow chart of a process for producing layers of an electrochemical cell according to an embodiment.

[0016] [Diagram 3] FIG. 3 is a flow chart plot of performance data relating to capacity retention for electrochemical cells constructed in accordance with embodiments.

[0017] [Figure 4] 4A and 4B show an exemplary electrochemical cell layer made without (FIG. 4A) and with (FIG. 4B) a rheology-modifying component. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In the following description, specific details are provided to convey a thorough understanding of various embodiments of the present invention. However, upon reading and understanding the specification, claims, and drawings, those skilled in the art will understand that some embodiments of the present invention can be practiced without adhering to some of the specific details set forth herein. Moreover, in order to avoid obscuring the present invention, some well-known methods, processes, equipment, and systems that find application in the various embodiments described herein are not disclosed in detail.

[0019] Concentrations, amounts, and other numerical data may be expressed or presented in a range format herein. It should be understood that such range formats are merely used for convenience and brevity, and should be interpreted flexibly to include not only the numerical values ​​expressly recited as the limits of the range, but also all individual numerical values ​​or subranges subsumed within the range as if each numerical value and subrange were expressly recited. As an example, the numerical range "about 2 to about 50" should be interpreted not only to include the explicitly recited values ​​of 2 to 50, but also to include all individual values ​​and subranges within the stated range. Thus, included within this numerical range are individual values ​​such as, for example, 2, 2.4, 3, 3.7, 4, 5.5, 10, 10.1, 14, 15, 15.98, 20, 20.13, 23, 25.06, 30, 35.1, 38.0, 40, 44, 44.6, 45, 48, and subranges such as, for example, 1-3, 2-4, 5-10, 5-20, 5-25, 5-30, 5-35, 5-40, 5-50, 2-10, 2-20, 2-30, 2-40, 2-50, etc. This same principle applies to ranges recited with only one numerical value as a minimum or maximum value. Moreover, such an interpretation should apply regardless of the breadth or nature of the range recited.

[0020] Although certain examples herein may be described with reference to solid electrolytes, it should be understood that the materials, methods and procedures described herein may be applied to electrochemical cells using gel electrolytes, semi-solid electrolytes, or combinations of liquid and solid electrolytes.

[0021] Described herein is a process for making one or more layers of an electrochemical cell using a rheologically modified slurry, and an electrochemical cell made therefrom. Generally, adding a polymer to modify the rheology of the slurry is not preferred because a large amount of the rheology modifying polymer must be added to significantly modify the rheology of the slurry. Generally, adding a large amount of the rheology modifying component reduces the performance of the electrochemical cell, for example, by increasing the resistance of the cell. Thus, the rheology modifying component must be removed from the slurry to maintain the performance of the cell, which increases processing time and cost. The inventors have surprisingly found that the rheology of the slurry can be significantly modified by including a relatively small amount of the rheology modifying component described herein, thereby making the processing of the slurry more efficient without significantly impairing the performance of the electrochemical cell.

[0022] 1 is a simplified schematic diagram of the layer structure of an exemplary electrochemical cell 100 including a solid electrolyte. The electrochemical cell 100 may include multiple layers including, but not limited to, an anode layer 110, an electrolyte layer 120 (also referred to herein as a "separator layer"), a cathode layer 130, and a current collector layer 140.

[0023] The anode layer 110 may be formed from a lithium metal or lithium alloy foil, which may include one or more of metallic sodium (Na) or metallic potassium (K). In one embodiment, the lithium metal foil may include one or more of alkaline earth metals, such as magnesium (Mg) and calcium (Ca). In another embodiment, the lithium foil may include aluminum (Al), indium (In), silver (Ag), gold (Au), or zinc (Zn).

[0024] In further embodiments, the lithium may be deposited on a metal foil, which may function as a current collector similar to current collector layer 140. The metal foil may include one or more of copper (Cu), aluminum (Al), nickel (Ni), titanium (Ti), stainless steel, magnesium (Mg), iron (Fe), zinc (Zn), indium (In), germanium (Ge), silver (Ag), platinum (Pt), or gold (Au). In some embodiments, the metal foil may have a thickness of about 6 μm to about 10 μm; for example, about 6 μm, about 7 μm, about 8 μm, about 9 μm, or about 10 μm. In preferred embodiments, the metal foil includes stainless steel or copper.

[0025] In one embodiment, the anode layer 110 is made of silicon (Si), tin (Sn), germanium (Ge) graphite, Li 4 Ti 5 O 12 The anode active material may comprise one or more materials such as cellulose acetate (CuO), cellulose ester (CuO), or other known anode active materials.

[0026] In some embodiments, the anode layer 110 can further include one or more conductive additives. The conductive additives can include metal powders, fibers, filaments, or any other materials known to conduct electrons. In some aspects, the one or more conductive additives can include one or more conductive carbon materials, such as carbon fibers, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, and carbon nanotubes. In some embodiments, the conductive additive can be present in the anode layer in an amount of about 3 wt.%.

[0027] In some embodiments, the conductive additive can be present in the anode layer in an amount of from about 0% to about 99% by weight, more preferably from about 0% to about 20% by weight, and even more preferably from about 0% to about 10% by weight.

[0028] In some embodiments, the anode layer 110 may further include one or more solid electrolytes. The one or more solid electrolytes may include oxides, oxysulfides, sulfides, halides, nitrides, or any other solid electrolytes known in the art. In some preferred embodiments, the one or more solid electrolytes may include a sulfide solid electrolyte; that is, a solid electrolyte having at least one sulfur component. In some embodiments, the one or more solid electrolytes may include a combination of one or more materials, such as the following: Li 2 SP 2 S 5 ,Li 2 SP 2 S 5 - LiI, Li 2 SP 2 S 5 -GeS 2 , Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 SP 2 S 5 -LiI-LiBr, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 SS-SiS 2 -LiCl.Li 2 SS-SiS 2 -B 2 S 3 - LiI, Li 2 SS-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -Z m S n(Here, m and n are positive numbers, and Z is Ge, Zn, or Ga), Li 2 S - GeS 2 、Li 2 S - S - SiS 2 -Li 3 PO 4 、及びLi 2 S - S - SiS 2 -Li x MO y (Here, x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In).

[0029] In another embodiment, the solid electrolyte is Li 3 PS 4 、Li 4 P 2 S 6 、Li 7 P 3 S 11 、Li 10 GeP 2 S 12 、Li 10 SnP 2 S 12 Among these, it can be one or more. In a further embodiment, the solid electrolyte is Li 6 PS 5 Cl、Li 6 PS 5 Br、Li 6 PS 5 I、or a formula Li 7-y PS 6-y X y Here, "X" represents at least one halogen and / or at least one pseudohalogen, 0 < y ≦ 2.0, the halogen can be one or more of F, Cl, Br, I, and the pseudohalogen can be one or more of N, NH, NH 2 、NO、NO 2 、BF 4 、BH 4 、AlH 4 、CN、and SCN. In yet another embodiment, the solid electrolyte is of the formula Li 8-y-z P 2 S 9-y-z X y Wz wherein "X" and "W" represent at least one halogen and / or at least one pseudohalogen, with 0≦y≦1 and 0≦z≦1, the halogen may be one or more of F, Cl, Br, I, and the pseudohalogen may be N, NH, NH 2 , NO, NO 2 , B.F. 4 , B.H. 4 , AlH 4 , CN, and SCN.

[0030] In some embodiments, the solid electrolyte can be present in anode layer 110 in an amount from about 0% to about 50% by weight, more preferably from about 0% to about 40% by weight.

[0031] The anode layer 110 may further include one or more binders or polymers. In some embodiments, the binder or polymer may include fluororesins containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof as structural units. In some additional embodiments, the binder or polymer may include homopolymers, such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), and polytetrafluoroethylene (PTFE), as well as binary copolymers, such as copolymers of VdF and HFP, such as poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP). In another embodiment, the polymer or binder can be one or more thermoplastic elastomers, such as, but not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate)nitrile-butadiene rubber (PMMA-NBR), etc. In a further embodiment, the polymer or binder can be one or more acrylic resins, such as, but not limited to, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, etc. In yet another embodiment, the polymer or binder can be one or more polycondensation polymers, such as, but not limited to, polyurea, polyamide paper, polyimide, polyester, etc. In yet another embodiment, the polymer or binder can be one or more nitrile rubbers, such as, but not limited to, acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), and mixtures thereof.In some embodiments, the binder or polymer may include one or more rheology modifying components. In some preferred embodiments, when the binder or polymer includes one or more rheology modifying components, the binder or polymer further includes one or more additional binders or polymers that are not rheology modifying components.

[0032] In some embodiments, the binder or polymer can be present in the anode layer 110 in an amount of about 0% to about 20% by weight. In some additional embodiments, the binder or polymer can be present in the anode layer 110 in an amount of about 0% to about 5% by weight, about 5% to about 10% by weight, about 10% to about 15% by weight, about 15% to about 20% by weight, about 0% to about 10% by weight, about 0% to about 15% by weight, or about 5% to about 15% by weight.

[0033] In some embodiments, the anode layer 110 can have a thickness of about 20 μm to about 40 μm. For example, the anode layer can have a thickness of about 20 μm, about 21 μm, about 22 μm, about 23 μm, about 24 μm, about 25 μm, about 26 μm, about 27 μm, about 28 μm, about 29 μm, about 30 μm, about 31 μm, about 32 μm, about 33 μm, about 34 μm, about 35 μm, about 36 μm, about 37 μm, about 38 μm, about 39 μm, or about 40 μm. In an exemplary embodiment, the anode layer includes lithium metal having a thickness of 34 μm.

[0034] The electrolyte layer 120 (also referred to herein as a "separator layer") may include one or more solid electrolytes. The one or more solid electrolytes may include an oxide, an oxysulfide, a sulfide, a halide, a nitride, or any other solid electrolyte known in the art. In some preferred embodiments, the one or more solid electrolytes may include a sulfide solid electrolyte. In some aspects, the one or more sulfide solid electrolytes may include one or more combinations of materials, such as the following: Li 2 SP 2 S 5 , Li 2 SP 2 S 5- LiI, Li 2 SP 2 S 5 -GeS 2 , Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 SP 2 S 5 -LiI-LiBr, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 SS-SiS 2 -LiCl, Li 2 SS-SiS 2 -B 2 S 3 - LiI, Li 2 SS-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is Ge, Zn, or Ga), Li 2 S-GeS 2 , Li 2 SS-SiS 2 -Li 3 PO 4 , and Li 2 SS-SiS 2 -Li x MO y (wherein x and y are positive numbers and M is P, Si, Ge, B, Al, Ga, or In). In some embodiments, the one or more solid electrolyte materials are Li 3 P.S. 4 , Li 4 P 2 S6 and Li 7 P 3 S 11 and Li 10 GeP 2 S 12 and Li 10 SnP 2 S 12 may be. In another embodiment, one or more solid electrolyte materials are Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I, or of the formula Li 7-y PS 6-y X y wherein "X" represents at least one halogen and / or at least one pseudohalogen, 0 < y ≦ 2.0, the halogen may be one or more of F, Cl, Br, I, and the pseudohalogen is N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN, and one or more of SCN. In another embodiment, one or more solid electrolyte materials are of the formula Li 8-y-z P 2 S 9-y-z X y W z wherein "X" and "W" represent at least one halogen and / or at least one pseudohalogen, 0 ≦ y ≦ 1 and 0 ≦ z ≦ 1, the halogen may be one or more of F, Cl, Br, I, and the pseudohalogen is N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN, and one or more of SCN.

[0035] The electrolyte layer 120 may further include one or more binders or polymers. In some embodiments, the binder or polymer may include fluororesins containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof as structural units. Specific examples include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), and polytetrafluoroethylene (PTFE), as well as binary copolymers such as copolymers of VdF and HFP, such as poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP). In another embodiment, the polymer or binder can be one or more thermoplastic elastomers, such as, but not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate)nitrile-butadiene rubber (PMMA-NBR), etc. In a further embodiment, the polymer or binder can be one or more acrylic resins, such as, but not limited to, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, etc. In yet another embodiment, the polymer or binder can be one or more polycondensation polymers, such as, but not limited to, polyurea, polyamide paper, polyimide, polyester, etc. In yet another embodiment, the polymer or binder can be one or more nitrile rubbers, such as, but not limited to, acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), and mixtures thereof.In some embodiments, the binder or polymer may include one or more rheology modifying components. In some preferred embodiments, when the binder or polymer includes one or more rheology modifying components, the binder or polymer further includes one or more additional binders or polymers that are not rheology modifying components.

[0036] In some embodiments, the binder or polymer may be present in the anode layer 110 in an amount of about 0 wt% to about 20 wt%. In some additional embodiments, the binder or polymer may be present in the anode layer 110 in an amount of about 0 wt% to about 5 wt%, about 5 wt% to about 10 wt%, about 10 wt% to about 15 wt%, about 15 wt% to about 20 wt%, about 0 wt% to about 10 wt%, about 0 wt% to about 15 wt%, or about 5 wt% to about 15 wt%.

[0037] In some embodiments, the electrolyte layer 120 may have a thickness of about 20 - 40 μm. For example, the electrolyte layer 120 may have a thickness of about 20 μm, about 21 μm, about 22 μm, about 23 μm, about 24 μm, about 25 μm, about 26 μm, about 27 μm, about 28 μm, about 29 μm, about 30 μm, about 31 μm, about 32 μm, about 33 μm, about 34 μm, about 35 μm, about 36 μm, about 37 μm, about 38 μm, about 39 μm, or about 40 μm.

[0038] Examples of the cathode layer 130 may include a cathode active material such as nickel - manganese - cobalt (e.g., "NMC"), which is Li(Ni a Co b Mn c )O 2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), or for example, NMC111 (LiNi 0.33 Mn 0.33 Co 0.33 O 2 ), NMC433 (LiNi 0.4 Mn 0.3 Co 0.3 O 2 ), NMC532 (LiNi 0.5 Mn 0.3 Co 0.2O 2 )、 NMC622 (LiNi 0.6 Mn 0.2 Co 0.2 O 2 )、 NMC811 (LiNi 0.8 Mn 0.1 Co 0.1 O 2 )、 or a combination thereof, and can be represented as such. In another embodiment, the cathode active material is one or more coated or uncoated metal oxides, such as V 2 O 5 、 V 6 O 13 、 MoO 3 、 LiCoO 2 、 LiNiO 2 、 LiMnO 2 、 LiMn 2 O 4 、 LiNi 1-Y Co Y O 2 、 LiCo 1-Y Mn Y O 2 、 LiNi 1-Y Mn Y O 2 (0 ≦ Y < 1), Li(Ni a Co b Mn c )O 4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-Z Ni Z O 4 、 LiMn 2-Z Co Z O 4 (0 < Z < 2), LiCoPO 4 、 LiFePO 4 、 CuO, Li(Ni a Co b Al c )O 2 (0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), or one or more coated or uncoated metal oxides such as, but not limited to, combinations thereof. In yet another embodiment, the cathode active material is one or more coated or uncoated metal sulfides, such as titanium sulfide (TiS 2), molybdenum sulfide (MoS 2 ), iron sulfide (FeS, FeS 2 ), copper sulfide (CuS), and nickel sulfide (Ni 3 S 2 ), or combinations thereof.

[0039] The cathode layer 130 may further include one or more conductive additives. The conductive additives may include metal powders, fibers, filaments, or any other materials known to conduct electrons. In some embodiments, the one or more conductive additives may include one or more conductive carbon materials, such as carbon fibers, graphite, graphene, carbon black, conductive carbon, amorphous carbon, VGCF, and carbon nanotubes. In some embodiments, the conductive additive may be present in the cathode layer in an amount of about 3% by weight.

[0040] In some embodiments, the conductive additive can be present in cathode layer 130 in an amount of from about 1% to about 10% by weight, more preferably from about 1% to about 8% by weight, and even more preferably from about 1% to about 5% by weight.

[0041] The cathode layer 130 may further include one or more solid electrolytes. The one or more solid electrolytes may include oxides, oxysulfides, sulfides, halides, nitrides, or any other solid electrolytes known in the art. In some preferred embodiments, the one or more solid electrolytes may include a sulfide solid electrolyte. In some embodiments, the solid electrolyte includes one or more combinations of materials, such as, for example, Li2S-P 2 S 5 , Li 2 SP 2 S 5 - LiI, Li 2 SP 2 S 5 -GeS 2 , Li 2 SP 2 S 5-Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 SP 2 S 5 -LiI-LiBr, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 SS-SiS 2 -LiCl, Li 2 SS-SiS 2 -B 2 S 3 - LiI, Li 2 SS-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -Z m S n (wherein m and n are positive numbers, and Z is Ge, Zn, or Ga), Li 2 S-GeS 2 , Li 2 SS-SiS 2 -Li 3 PO 4 , and Li 2 SS-SiS 2 -Li x MO y (wherein x and y are positive numbers and M is P, Si, Ge, B, Al, Ga, or In). In another embodiment, the solid electrolyte is Li 3 P.S. 4 , Li 4 P 2 S 6 , Li 7 P 3 S 11 , Li 10 GeP 2 S 12 , Li 10 SnP2 S 12 Among these, one or more may be included. In a further embodiment, the solid electrolyte is Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I, or a compound represented by the formula Li 7-y PS 6-y X y wherein one or more of them may be included. Here, "X" represents at least one halogen and / or at least one pseudohalogen, 0 < y ≦ 2.0, at least one halogen may be one or more of F, Cl, Br, and I, and at least one pseudohalogen may be one or more of N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN, and SCN. In yet another embodiment, the solid electrolyte is a compound represented by the formula Li 8-y-z P 2 S 9-y-z X y W z (where "X" and "W" represent at least one halogen element and / or at least one pseudohalogen, 0 ≦ y ≦ 1 and 0 ≦ z ≦ 1), the halogen may be one or more of F, Cl, Br, and I, and the pseudohalogen may be one or more of N, NH, NH 2 , NO, NO 2 , BF 4 , BH 4 , AlH 4 , CN, and SCN).

[0042] In some embodiments, the solid electrolyte may be present in the cathode layer 130 in an amount of about 5 wt% to about 20 wt%, more preferably about 10 wt% to about 18 wt%.

[0043] The cathode layer 130 may further include one or more of a binder or polymer. In some embodiments, the binder or polymer may include a fluororesin containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof as structural units. Specific examples include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), and polytetrafluoroethylene (PTFE), and binary copolymers such as copolymers of VdF and HFP, such as poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP). In another embodiment, the polymer or binder can be one or more thermoplastic elastomers, such as, but not limited to, styrene-butadiene rubber (SBR), styrene-butadiene-styrene copolymer (SBS), styrene-isoprene block copolymer (SIS), styrene-ethylene-butylene-styrene (SEBS), polyacrylonitrile (PAN), nitrile-butylene rubber (NBR), polybutadiene, polyisoprene, poly(methacrylate)nitrile-butadiene rubber (PMMA-NBR), etc. In a further embodiment, the polymer or binder can be one or more acrylic resins, such as, but not limited to, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyisopropyl (meth)acrylate, polyisobutyl (meth)acrylate, polybutyl (meth)acrylate, etc. In yet another embodiment, the polymer or binder can be one or more polycondensation polymers, such as, but not limited to, polyurea, polyamide paper, polyimide, polyester, etc. In yet another embodiment, the polymer or binder can be one or more nitrile rubbers, such as, but not limited to, acrylonitrile-butadiene rubber (ABR), polystyrene nitrile-butadiene rubber (PS-NBR), and mixtures thereof.In some embodiments, the binder or polymer may include one or more rheology modifying components. In some preferred embodiments, when the binder or polymer includes one or more rheology modifying components, the binder or polymer further includes one or more additional binders or polymers that are not rheology modifying components.

[0044] In some embodiments, the binder or polymer may be present in cathode layer 130 in an amount of from about 0% to about 5%. In some additional embodiments, the binder or polymer may be present in cathode layer 130 in an amount of from about 0% to about 2.5%, from about 2.5% to about 5%, from about 0% to about 1%, from about 0% to about 2%, from about 0% to about 3%, or from about 0% to about 4%. In exemplary embodiments, the binder or polymer may be present in cathode layer 130 in an amount of from about 0.25% to about 2%.

[0045] The current collector layer 140 may comprise one or more of aluminum (Al), nickel (Ni), titanium (Ti), stainless steel, magnesium (Mg), iron (Fe), zinc (Zn), indium (In), germanium (Ge), silver (Ag), platinum (Pt), and gold (Au). In some embodiments, a second current collector layer may be disposed adjacent to the anode layer. In a preferred embodiment, the current collector layer 140 comprises aluminum.

[0046] In some embodiments, the current collector layer 140 can have a thickness of about 10 μm to about 20 μm. For example, the current collector layer 140 can have a thickness of about 10 μm, about 11 μm, about 12 μm, about 13 μm, about 14 μm, about 15 μm, about 16 μm, about 17 μm, about 18 μm, about 19 μm, or about 20 μm. In an exemplary embodiment, the current collector layer 140 comprises aluminum having a thickness of about 12 to 14 μm.

[0047] FIG. 2 is a flow chart of a process for producing a layer of an electrochemical cell and will be described in relation to the cathode layer 130 of FIG. 1. It should be noted that this process may also be used to produce an anode layer with appropriate modifications. For example, prior to forming the anode layer, the silicon material used for the anode production may be treated to reduce its grain size. This grain size reduction step may occur at any stage prior to the casting / coating step. This grain size reduction step includes, but is not limited to, milling / grinding of the silicon material alone, the silicon material with conductive additives, the silicon material with solid electrolyte material, the silicon material with binder, or any combination thereof. Thus, where terms such as catholyte, catholyte slurry, and cathode layer are mentioned, they are not limiting and the respective terms such as anolyte, anolyte slurry, and anode layer may be substituted.

[0048] In one embodiment, the process 200 begins with a preparation step 210, where any preparatory actions may be performed, such as pre-dissolving the binder in the solution, selecting and dividing the components, and preparing the equipment. In one aspect, the solvent may be selected from one of the following, but is not limited to: aprotic hydrocarbons, esters, ethers, or nitriles. In another aspect, the aprotic hydrocarbon may be selected from one of the following, but is not limited to: xylene, toluene, benzene, methylbenzene, hexane, heptane, octane, alkanes, isoparaffinic hydrocarbons, or combinations thereof. In another aspect, the ester may be selected from one of the following, but is not limited to: butyl butyrate, isobutyl isobutyrate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, or combinations thereof. In another aspect, the ether may be selected from one of the following, but is not limited to: diethyl ether, dibutyl ether, benzyl ether, or combinations thereof. In another embodiment, the nitrile may be selected from one of the following, but is not limited to: acetonitrile, propionitrile, butyronitrile, pyrrolidine, or a combination thereof.

[0049] After any initial preparation, the process 200 proceeds to step 220, where a first component and a solvent are mixed to form a slurry. As used herein, a slurry refers to a semi-liquid mixture of solid particles suspended in a solvent. The first component of a catholyte slurry may include a solvent, a solid electrolyte, and a binder or polymer. The mixing action may be provided by known means.

[0050] Mixing may occur prior to the addition of one or more rheology modifying components to the mixed slurry during step 230. The mixing prior to addition is performed to initially wet the catholyte slurry. The rheology modifying components may be selected from compounds such as, but not limited to, poly(styrene-butadiene-styrene) block copolymers (SBS; styrene-butadiene-styrene rubber, also referred to herein as "SBR"), poly(styrene-isoprene-styrene) block copolymers (SIS), or poly(styrene-ethylene-butylene-styrene) block copolymers (SEBS).

[0051] The rheology modifying component may be added to the slurry at less than 5% by weight of the slurry. Thus, the rheology modifying component may be present in the resulting electrochemical cell layer in an amount of less than 5% by weight. In some embodiments, the rheology modifying component may be present in the electrochemical cell layer in an amount of less than 5% by weight, less than 4% by weight, less than 3% by weight, less than 2% by weight, less than 1% by weight, or less than 0.5% by weight. In some additional embodiments, the rheology modifying component may be present in the electrochemical cell layer in an amount of about 0% to about 5% by weight, about 0% to about 4% by weight, about 0% to about 3% by weight, or about 0% to about 2% by weight. In an exemplary embodiment, the electrochemical cell layer is a cathode layer and the rheology modifying component is present in an amount of about 0.25% by weight. In another exemplary embodiment, the electrochemical cell layer is an anode layer and the rheology modifying component is present in an amount of about 2% by weight.

[0052] In some embodiments, the rheology modifying component may be added to the solid electrolyte slurry at less than 5 wt%. In some embodiments, the rheology modifying component may be added to the solid electrolyte slurry at less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some additional embodiments, the rheology modifying component may be added to the solid electrolyte slurry at about 0 wt% to about 5 wt%, more preferably about 0.2 wt% to about 2 wt%. In an exemplary embodiment, the rheology modifying component may be added to the solid electrolyte slurry at about 0.25 wt%.

[0053] In some embodiments, the rheology modifying component may be added to the cathode slurry at less than 5 wt. %. In some embodiments, the rheology modifying component may be added to the cathode slurry at less than 5 wt. %, less than 4 wt. %, less than 3 wt. %, less than 2 wt. %, less than 1 wt. %, or less than 0.5 wt. %. In some additional embodiments, the rheology modifying component may be added to the cathode slurry at about 0 wt. % to about 5 wt. %, more preferably about 0.2 wt. % to about 2 wt. %. In an exemplary embodiment, the rheology modifying component may be added to the cathode slurry at about 1 wt. %.

[0054] In some embodiments, the rheology modifying component may be added to the anode slurry at less than 5 wt%. In some embodiments, the rheology modifying component may be added to the anode slurry at less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt%. In some additional embodiments, the rheology modifying component may be added to the anode slurry at about 0 wt% to about 5 wt%, more preferably about 0.5 wt% to about 4 wt%, and even more preferably about 1 wt% to about 3 wt%. In an exemplary embodiment, the rheology modifying component may be added to the anode slurry at about 2 wt%.

[0055] In some embodiments, rheology modifying components may be added in amounts less than 5% by weight or other amounts as needed to reduce the viscosity while maintaining a high solid-to-solvent ratio. A high solid-to-solvent ratio is favorable for drying the slurry because it means less solvent is needed and less solvent to evaporate and recover. Furthermore, if the slurry has a low solid-to-solvent ratio, the slurry may not dry uniformly. For example, if the coated slurry is dried using forced air drying, the top surface of the slurry dries first. As the solvent in the layer evaporates, it is pushed toward the surface, causing cracks (often called "mud cracks") in the newly dried surface, as shown in FIG. 4A. By reducing the amount of solvent in the slurry, the layer can be dried in a more uniform manner, thus preventing mud cracks, as shown in FIG. 4B.

[0056] In another embodiment, suitable viscosity values ​​range from about 100 cP to about 5000 cP, from about 500 cP to about 3000 cP, or from about 1000 cP to about 2000 cP (about 0.1 Pa·s to about 5 Pa·s, from about 0.5 Pa·s to about 3 Pa·s, or from about 1 Pa·s to about 2 Pa·s). In some additional embodiments, the slurry can have a viscosity of 100 cP to 4000 cP, 100 cP to 3000 cP, 100 cP to 2000 cP, 500 cP to 4000 cP, 500 cP to 3000 cP, 500 cP to 2000 cP, 1000 cP to 5000 cP, 1000 cP to 4000 cP, or 1000 cP to 3000 cP (0.1 Pa·s to 4 Pa·s, 0.1 Pa·s to 3 Pa·s, 0.1 Pa·s to 2 Pa·s, 0.5 Pa·s to 4 Pa·s, 0.5 Pa·s to 3 Pa·s, 0.5 Pa·s to 2 Pa·s, 1 Pa·s to 5 Pa·s, 1 Pa·s to 4 Pa·s, or 1 Pa·s to 3 Pa·s). Suitable solids to solvent ratios range from about 10% to about 90%, about 20% to about 80%, or about 30% to about 70% by weight for the exemplary slurries. In some additional embodiments, the solids to solvent ratio can be about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, or about 90%. In preferred embodiments, the slurry exhibits no mud cracking when the slurry is dried. In other preferred embodiments, the slurry is substantially resistant to mud cracking when the slurry is dried, as depicted in FIG. 4B. In yet other preferred embodiments, the dried slurry is substantially free of mud cracking and / or surface cracking.

[0057] In some additional embodiments, the power law coefficient of the slurry can be less than 1; preferably, the power law coefficient of the slurry can be from about 0.25 to about 0.75. In some examples, the power law coefficient of the slurry can be about 0.9, about 0.8, about 0.7, about 0.6, about 0.5, about 0.4, about 0.3, about 0.2, or about 0.1.

[0058] After modifying the rheology, the catholyte slurry may be milled during step 240 to reduce the particle size of the electrolyte in the slurry to a desired size. The milling may be accomplished by conventional methods. Adding the rheology modifying component prior to milling may allow the milling of the catholyte slurry to be improved, such as allowing for more uniform mixing of the catholyte slurry and a reduced amount of processing steps, as compared to milling all components of the catholyte slurry first and mixing the components at a later step. The addition of the rheology modifying component may prevent agglomeration of particles in the slurry. Without the addition of the rheology modifying component to the catholyte slurry, milling may be inhibited, making it difficult to reduce the particle size of the electrolyte.

[0059] In some embodiments, the particle size of the solids in the slurry may be less than about 1 μm. As used herein, particle size refers to the median diameter (D 50 ) Methods for measuring the median particle size are well known in the art. In some examples, the particle size of the solids in the slurry can be about 0.9 μm, about 0.8 μm, about 0.7 μm, about 0.6 μm, about 0.5 μm, about 0.4 μm, about 0.3 μm, about 0.2 μm, about 0.1 μm, or less than about 0.1 μm.

[0060] In another embodiment, following milling, a second component of the slurry may be added during step 250. The second slurry component may include an active cathode material, a conductive additive, and an additional binder. Additional rheology modifying components may be added to the catholyte slurry to modify the final rheology of the catholyte slurry to obtain a suitable viscosity and power law coefficient for uniform coating. Adding rheology modifying components to control the final rheology for coating allows the catholyte slurry to change quickly from a preferred milled consistency to a cast / coated consistency. During step 260, the catholyte slurry may be coated onto a suitable carrier or substrate, such as aluminum, carbon coated aluminum, copper or carbon coated copper current collector 140 of FIG. 1. Similar carriers may be used for the anode slurry, especially copper based carriers. The slurry and carrier may be treated to harden and / or dry. The resulting layered structure may be incorporated into an electrochemical cell during step 270. Process 200 may complete at step 280.

[0061] The catholyte slurry as produced by process 200 has an improved rheology, which may involve an increase in viscosity and / or power law coefficient of about 100 cP to about 5000 cP (about 0.1 Pa·s to about 5 Pa·s). Rheology modifying components may be added at multiple stages of the production of the slurry, thereby modifying the rheology to meet the needs of intermediate process conditions. Various embodiments of the present disclosure may include some or all of the additions at various stages, alone or in combination. As discussed above, rheology modifying components may be added to the catholyte slurry to change the rheology to an improved state for milling, and may be added subsequently to modify the final rheology of the catholyte slurry to create a coatable or castable slurry. The modified slurry provides reduced susceptibility to separation and thickness changes, both of which lead to poor cycling performance of cells constructed from less suitable materials.

[0062] FIG. 3 is a plot of performance data relating to capacity retention for electrochemical cells constructed according to embodiments of the present disclosure. As shown in plot 300, the addition of SBS and SIS polymers provides a capacity retention advantage over the use of neither polymer. In one embodiment, for the constructed samples, 0.27 wt% SBS and 0.25 wt% SIS were included in the modified cathode layer. Data labeled "SBS" was obtained from a cathode composite including 80 wt% active material, 16.73 wt% solid electrolyte powder, 3 wt% carbon-based conductive additive, 2 wt% SEBS, and 0.27 wt% SBS. Data labeled "PIP" was obtained from a cathode composite including 80 wt% active material, 16.75 wt% solid electrolyte powder, 3 wt% carbon-based conductive additive, 2 wt% SEBS, and 0.25 wt% SIS. Data marked "None" were obtained from a cathode composite containing 80 wt% active material, 17 wt% solid electrolyte powder, 3 wt% carbon-based conductive additive, and 2 wt% SEBS. In the samples constructed, both SBS and SIS were dissolved in xylene before adding to the other components of the slurry and adjusting the amounts to obtain a power law response greater than 0.6. For the data shown, the cells were cycled at 70C under C / 10 conditions with voltages between 2.5 and 4.0 VDC.

[0063] In some embodiments, the cathode layers of the present disclosure may have increased active cathode discharge capacity as compared to cathode layers that do not include a rheology-modifying component and that are produced using methods previously known in the art.

[0064] Certain limitations may apply to the use of the rheology modifying components mentioned above. In particular, if the electrolyte used does not contain sulfur participating in chemical bonding, SBS may not exert the desired effect. In one embodiment, the SBS may not have a styrene content greater than 50% or a butadiene content less than 50%. In another embodiment, the SBS may not have a styrene content greater than 30% or a butadiene content less than 70%. Without wishing to be bound by theory, a lower weight percentage of the rheology modifying component may allow the cathode slurry to maintain higher electrical and ionic conductivity, resulting in improved cell performance. The use of the rheology modifying component modifies the rheology of the slurry without the need for excess solvent, which may react with the electrolyte and reduce cell performance, and may complicate slurry processing and coating; because excess solvent must be removed to adjust the slurry viscosity before coating.

[0065] The features described above and in the following claims may also be combined in various ways without departing from the scope of this specification. It should therefore be noted that the matters contained in the above description or shown in the accompanying drawings should be interpreted as illustrative and not in a limiting sense. The above-described embodiments should be considered as examples of the present invention, rather than limiting the scope of the present invention. In addition to the embodiments of the invention described above, a review of the detailed description and the accompanying drawings will show that other embodiments of such invention exist. Thus, many combinations, permutations, variations and modifications of the embodiments of the invention described above, not expressly provided herein, will nevertheless fall within the scope of such invention.

[0066] Exemplary embodiments

[0067] Embodiment 1: An electrochemical cell layer comprising: a solid electrolyte; and a rheology modifying component selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS); wherein the rheology modifying component is present in an amount less than 5% by weight of the electrochemical cell layer.

[0068] Embodiment 2: The electrochemical cell layer of embodiment 1; wherein the layer is a separator layer comprising at least one additional binder or polymer.

[0069] Embodiment 3: The electrochemical cell layer of embodiment 2; wherein the binder or polymer is at least one binder or polymer selected from the group consisting of polystyrene, polyvinylidene fluoride (PVdF), and poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP).

[0070] Embodiment 4: The electrochemical cell layer of embodiment 1; wherein the layer is a cathode layer comprising a cathode active material, a binder or polymer, and a conductive additive.

[0071] Embodiment 5: The electrochemical cell of embodiment 4; wherein the cathode active material is NMC, LiFePO 4 , LiCoO 2 , NCA, NMA, LMO, and iron sulfide.

[0072]

[0023] Embodiment 6: The electrochemical cell layer of embodiment 4; wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0073] Embodiment 7: The electrochemical cell layer of embodiment 1; wherein the layer is an anode layer comprising an anode active material, a binder or polymer, and a conductive additive.

[0074] Embodiment 8: The electrochemical cell of embodiment 7; wherein the anode active material is selected from the group consisting of Si, Si alloys, graphite, Sn, Li, and lithium alloys.

[0075]

[0031] Embodiment 9: The electrochemical cell layer of embodiment 7; wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0076] Embodiment 10: The electrochemical cell layer of embodiment 1; wherein the rheology modifying component is present in an amount less than 2% by weight of the electrochemical cell layer.

[0077] Embodiment 11: A method of making an electrochemical cell layer comprising: forming a slurry of a solid electrolyte; a rheology modifying component selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS), in an amount of less than 5% by weight of the solid composition of the slurry; and a solvent; and coating the slurry on a substrate to form an electrochemical cell layer.

[0078]

[0041] Embodiment 12: The method of embodiment 11; wherein the layer is a cathode layer and the slurry further comprises a cathode active material, a binder or polymer, and a conductive additive.

[0079] Embodiment 13: The method of embodiment 12, wherein the cathode active material is NMC, LiFePO 4 , LiCoO 2 , NCA, NMA, LMO, and iron sulfide.

[0080]

[0041] Embodiment 14: The method of embodiment 12, wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0081] Embodiment 15: The method of embodiment 11; wherein the layer is an anode layer and the slurry further comprises an active material, a binder or polymer, and a conductive additive.

[0082] Embodiment 16: The method of embodiment 15, wherein the anode active material is selected from the group consisting of Si, Si alloys, graphite, Sn, Li, and lithium alloys.

[0083]

[0041] Embodiment 17: The method of embodiment 15, wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

[0084] Embodiment 18: The method of embodiment 11, wherein the rheology modifying component is present in an amount of less than 2% by weight of the solid composition of the slurry.

[0085] Embodiment 19: The method of embodiment 11, further comprising milling the slurry before coating it onto the substrate; wherein a rheology modifying component is added to the other components of the slurry before milling.

[0086]

[0046] Embodiment 20: The method of embodiment 11, wherein the solid electrolyte is a sulfide solid electrolyte comprising a lithium compound, a phosphorus compound, and a halogen.

[0087] Embodiment 21: The method of embodiment 11, wherein the solvent is selected from the group consisting of benzene, toluene, xylene, heptane, and isobutyl isobutyrate.

[0088] Embodiment 22: A composition comprising: a solvent; a solid electrolyte; a binder or polymer; and one or more rheology modifying components selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS; herein styrene-butadiene-styrene rubber, also referred to as "SBR"), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS); wherein the composition has a viscosity of about 100 cP to about 5000 cP (about 0.1 Pa·s to about 5 Pa·s).

[0089] Embodiment 23: The composition of embodiment 22, further comprising one of: (a) a cathode active material; or (b) an anode active material; and a conductive additive.

[0090] Embodiment 24: The composition of embodiment 22, wherein the solids to solvent ratio is from about 10% to about 90% by weight. EXAMPLES

[0091] Example 1: Rheology modification with SBS with different styrene to rubber ratios.

[0092] Experiments were conducted to determine the effect of different styrene to rubber (butadiene) ratios on the rheology of the slurry when using SBS as the rheology modifying component. Two cathode slurries were prepared to measure this effect, as described below.

[0093] The first slurry contained 80% NMC, 14.75% solid electrolyte material, 2.5% KS6, 0.5% C65, and 2% SEBS. The solids content of the slurry was 77.5%. To this slurry was added 0.25% SBS (Kraton D1102, S:R ratio=29:71). The viscosity of the slurry was 1059 cP (1.059 Pa s), and the slurry had a power law coefficient of 0.669.

[0094] The second slurry contained 80% NMC, 14.75% solid electrolyte material, 2.5% KS6, 0.5% C65, and 2% SEBS. The solids content of the slurry was 77.5%. To this slurry was added 0.25% SBS (Kraton D1155, S:R ratio=40:60). The viscosity of the slurry was 4152 cP (4.152 Pa s), and the slurry had a power law coefficient of 0.422.

[0095] The results show that when SBS with increasing percentage of rubber and decreasing percentage of styrene is added to the cathode slurry, the viscosity reduction is enhanced while the power law coefficient increases. Thus, the rheology modifying effect of SBS increases as the percentage of rubber in the SBS increases.

[0096] Example 2: Effect of SBS on the percentage of solids in the slurry

[0097] The effect of SBS on the percent solids required to make a castable slurry was investigated. Two separator slurries and two cathode slurries were prepared to determine the effect of SBS on the percent solids required to form a castable slurry.

[0098] A separator slurry was made containing solid electrolyte material and 2% SEBS. The solvent was a mixture of xylenes. To make the slurry castable, a solids content of 45% or less was required. The same slurry was then made with an addition of 0.25% SBS. To make the slurry castable, a solids content of 55% or less was required.

[0099] A cathode slurry was prepared containing NMC, carbon, and solid electrolyte material, where the solvent was a mixture of xylene. To make the slurry castable, a solids content of 72.5% or less was required. The same slurry was then prepared with an addition of 0.25% SBS. To make the slurry castable, a solids content of 81% or less was required.

[0100] These results show that the addition of SBS significantly increased the percent solids required to make a castable slurry.

[0101] The terms used herein generally have their ordinary meaning in the art, within the context of this disclosure and in the specific context in which each term is used. Alternative language and synonyms may be used for any one or more terms discussed herein, and no special meaning should be placed on a term whether it is detailed or discussed herein. In some cases, synonyms for a particular term are provided. The description of one or more synonyms does not exclude the use of other synonyms. The use of examples anywhere in this specification, including examples of any term discussed herein, is for illustrative purposes only and is not intended to further limit the scope and meaning of the disclosure or any example term. Similarly, this disclosure is not limited to the various embodiments provided herein.

[0102] As used herein, the terms "a," "an," and "the" are understood to encompass the plural as well as the singular. Thus, the term "a mixture thereof" also relates to "mixtures thereof," and the term "a component" also refers to "components."

[0103] In this specification, the term "about" is used to provide flexibility to the endpoints of a numerical range by providing the possibility that a given value may be "a little above" or "a little below" the endpoint. For example, the endpoint may be within 10%, 8%, 5%, 3%, 2%, or 1% of the recited value. Furthermore, for convenience and brevity, a numerical range of "about 50 mg / mL to about 80 mg / mL" should also be understood to provide support for the range "50 mg / mL to 80 mg / mL". The endpoint may also be based on the variability allowed by the appropriate regulatory agency, e.g., FDA, USP, etc.

[0104] In this disclosure, "comprises," "comprises," "containing," "having," and the like can have the meanings given to them in U.S. Patent Law, and can mean "comprises," "comprising," and the like, and are generally construed as open-ended terms. The terms "consisting of" or "consisting of" are closed terms and include only those components, structures, steps, and the like specifically recited with such terms, and in accordance with U.S. Patent Law. "Consisting essentially of" or "consisting essentially of" have the meanings generally given to them by U.S. Patent Law. In particular, such terms are generally closed terms, with the exception of permitting the inclusion of additional items, materials, components, steps, or elements that do not materially affect the basic and novel properties or functions of one or more items used in connection therewith. For example, trace elements that are present in a composition but do not affect the nature or properties of the composition are permitted when present under the language "consisting essentially of" even if they are not explicitly recited in the list of items following such terms. It is understood that when open-ended terms such as "comprising" or "including" are used in this specification, direct support should be given to the words "consisting essentially of" and "consisting of" as if expressly set forth above, and vice versa.

Claims

1. An electrochemical cell layer comprising: Cathode active material, A solid electrolyte; and a rheology modifying component comprising a poly(styrene-butadiene-styrene) block copolymer (SBS); Including, the rheology modifying component is present in an amount of less than 0.5% by weight of the electrochemical cell layer, and the SBS has a butadiene content of 50% or greater; Electrochemical cell layer.

2. 10. The electrochemical cell layer of claim 1, wherein the layer is implemented in an electrochemical cell stack, the electrochemical cell stack having a separator layer comprising at least one additional binder or polymer.

3. 3. The electrochemical cell layer of claim 2, wherein the binder or polymer is at least one binder or polymer selected from the group consisting of polystyrene, polyvinylidene fluoride (PVdF), and poly(vinylene difluoride-hexafluoropropylene) copolymer (PVdF-HFP).

4. The electrochemical cell layer of claim 1, further comprising a binder or polymer, and a conductive additive.

5. The cathode active material is NMC, LiFePO 4 , LiCoO 2 10. The electrochemical cell layer of claim 1, wherein the metal oxide is selected from the group consisting of iron oxide, iron sulfide, iron oxide ...

6. 5. The electrochemical cell layer of claim 4, wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

7. 10. The electrochemical cell layer of claim 1, wherein the layer is implemented in an electrochemical cell stack, the electrochemical cell stack having an anode layer comprising an anode active material, a binder or polymer, and a conductive additive.

8. 8. The electrochemical cell of claim 7, wherein the anode active material is selected from the group consisting of Si, Si alloys, graphite, Sn, Li, and lithium alloys.

9. 8. The electrochemical cell layer of claim 7, wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

10. 10. The electrochemical cell layer of claim 1, wherein the rheology modifying component is present in an amount of about 0.25% by weight of the electrochemical cell layer.

11. A method for producing an electrochemical cell layer, comprising: forming a slurry of: a solid electrolyte; a rheology modifying component selected from the group consisting of poly(styrene-butadiene-styrene) block copolymer (SBS), poly(styrene-isoprene-styrene) block copolymer (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymer (SEBS) in an amount of less than 5% by weight of the solid composition of the slurry; and a solvent; Coating the slurry onto a substrate to form the electrochemical cell layer.

12. The method of claim 11 , wherein the layer is a cathode layer and the slurry further comprises a cathode active material, a binder or polymer, and a conductive additive.

13. The cathode active material is NMC, LiFePO 4 , LiCoO 2 13. The method of claim 12, wherein the iron sulfide is selected from the group consisting of iron sulfide, iron sulph ...

14. 13. The method of claim 12, wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

15. The method of claim 11 , wherein the layer is an anode layer and the slurry further comprises an active material, a binder or polymer, and a conductive additive.

16. 16. The method of claim 15, wherein the anode active material is selected from the group consisting of Si, Si alloys, graphite, Sn, Li, and lithium alloys.

17. 16. The method of claim 15, wherein the conductive additive is selected from the group consisting of carbon black, graphite, graphene, VGCF, activated carbon, and carbon nanotubes.

18. 12. The method of claim 11, wherein the rheology modifying component is present in an amount of less than 2% by weight of the solid composition of the slurry.

19. 12. The method of claim 11, further comprising milling the slurry prior to coating the slurry on the substrate, wherein the rheology modifying component is added to other components of the slurry prior to milling.

20. 12. The method of claim 11, wherein the solid electrolyte is a sulfide solid electrolyte comprising a lithium compound, a phosphorus compound, and a halogen.

21. 12. The method of claim 11, wherein the solvent is selected from the group consisting of benzene, toluene, xylene, heptane, and isobutyl isobutyrate.

22. 1. A composition comprising: solvent; solid electrolyte; a binder or polymer; and one or more rheology modifying components selected from the group consisting of poly(styrene-butadiene-styrene) block copolymers (SBS; styrene-butadiene-styrene rubber, also referred to as "SBR"), poly(styrene-isoprene-styrene) block copolymers (SIS), and poly(styrene-ethylene-butylene-styrene) block copolymers (SEBS); having The composition has a viscosity of about 100 cP to about 5000 cP (about 0.1 Pa·s to about 5 Pa·s). composition.

23. 23. The composition of claim 22 further comprising: One of the following: (a) a cathode active material; or (b) an anode active material; and Conductive additive.

24. 23. The composition of claim 22, wherein the solids to solvent ratio is from about 10% to about 90% by weight.